Impact of Perfectionism and Resilience on Empathy in Medical Students: A Cross-Sectional Study. (June 2022) - Rafaqat, Wardah; Sami, Ashmal; Ibrahim, Muhammad Talal; Ibad, Hamza; Awais, Sheharbano; Memon, Ayesha; Shahbaz, Fatima Farrukh; Ahmed, Daniyaal; Zindani, Shahzaib; Leghari, Abdul Lateef; Saleem, Sarah
Empathy is a cognitive attribute that forms the cornerstone for good doctor–patient encounters. The formative period for the development of empathy toward patients begins with clinical encounters within medical school. An individual medical student's empathy levels may in part be a product of their resilience and perfectionist attitudes. A cross-sectional study with 320 medical students across all years of study was conducted to determine the correlation of perfectionism and resilience with clinical empathy in medical students. The JSE-S, CD-RISC 10, and APS-R scales were used to assess levels of empathy, resilience, and perfectionism, respectively. The study found that a positive correlation exists between resilience ( r = 0.174) and academic year with empathy, and a negative correlation exists between maladaptive perfectionism and empathy ( r = −0.138). The resilience score declined progressively as the year of study progressed with a statistically significant. Mean empathy scores were lowest in fifth-year students (96.8 ± 12.5) and highest in third-year students (107.8 ± 13.2). Further longitudinal studies are necessary to better understand the impact of resilience and perfectionism on empathy.